Effects of microclimate during transport on physiological indicators of market pig welfare: a systematic review with meta-analysis - Hernandez, Rick O.; Rocha, Artur O.; Cai, Chao; Erasmus, Marisa; Johnson, Jay S.; Brito, Luiz F. (Frontiers in Veterinary Science, 2025)
During transportation, microclimatic conditions can fluctuate significantly, affecting pigs’ thermal comfort and leading to compromised welfare and production losses. Although numerous studies have examined the effects of heat stress during transport on pig welfare and meat quality, it remains unclear whether these effects persist across varying transport scenarios and environmental conditions. Therefore, this systematic review and meta-analysis evaluated the effects of microclimate during transport on physiological welfare indicators in market pigs and summarized methodologies for assessing microclimate in commercial settings. Following PRISMA guidelines, 21 studies from three databases were used. Meta-regression analyses assessed microclimatic effects and trip duration on physiological indicators, including ultimate pH (pHu), creatine kinase (U/L), lactate (mmol/L), skin lesion score (0–5), skin temperature (°C), and blood cortisol (ng/mL). The studies retrieved used different equations to determine temperature-humidity index and enthalpy to describe microclimate dynamics. Ambient temperature was significantly associated with trailer temperature (β = 0.93 ± 0.12; p < 0.01). However, ambient relative humidity showed a lower magnitude association with trailer relative humidity (β = 0.51 ± 0.00; p < 0.001). Adverse microclimate conditions represented by high enthalpy (H) were associated with increases in creatine kinase (β = 3,715 ± 94.11; p < 0.001), lactate (β = 0.45 ± 0.12; p < 0.001), skin temperature (β = 0.10 ± 0.03; p < 0.01), and blood cortisol (β = 0.16 ± 0.08; p < 0.05). Short trips (<119 min) increased skin lesion score (β = 2.58 ± 0.43; p < 0.01), and medium trips (120–420 min) increased skin temperature (β = 6.36 ± 0.45; p < 0.001) and reduced cortisol levels (β = –11.36 ± 2.59; p < 0.01). In conclusion, trailer microclimates differ from ambient conditions and are strongly associated with physiological stress indicators in market pigs. Monitoring H may offer a more accurate representation of thermal load during transport, enabling threshold development for risk assessment. These consistent associations across diverse environments underscore the global nature of transport-related heat stress and the need for coordinated international welfare standards. Integrating compartment-level microclimate monitoring into transport protocols will improve welfare evaluation and support predictive risk models.